180k views
0 votes
48 POINTS! PLEASE HELP!
Show work please THANKS

48 POINTS! PLEASE HELP! Show work please THANKS-example-1

2 Answers

3 votes

Answer:

c

Explanation:

x times 3

User Jonnybinthemix
by
5.5k points
3 votes

Answer:

C multiply the first equation by 3

Explanation:

3x-y =5

2x+3y = 10

We want to eliminate y

Since the first equation has a negative 1y and the second equation has 3y

I would multiply the first equation by 3 and then the y's cancel

3(3x-y =5)

9x -3y = 15

2x+3y = 10

------------------

11x = 25

User Sheraz Ahmed
by
5.8k points